The Influence of Personnel Management and Organizational Structure on Work Effectiveness at Bamin Subsiverif Sikeu Polresta Tangerang Banten Regional Police - Cahyo Eko; Kemal Taufik; Sri Wahyuningsih (Dinasti Publisher, 2026)
The objectives of this study: 1) To determine the effect of Personnel Management on Work Effectiveness, 2) To determine the effect of Organizational Structure on Work Effectiveness, 3) To determine the effect of Personnel Management and Organizational Structure on Work Effectiveness. This is proven by the calculated t-value of 5.556 which is greater than the t-table of 1.997 at a significance level of 0.05, Organizational Structure has a significant effect on Member Work Effectiveness. The test results show a calculated t-value of 7.272, which is greater than the t-table of 1.997, so the hypothesis states that there is an influence of organizational structure on member work effectiveness can be accepted, Personnel Management and Organizational Structure simultaneously have a significant effect on Member Work Effectiveness. Based on the results of the F test, the calculated F-value is 60.361 which is greater than the F-table of 2.75 with a significance level of 0.000 <0.05. The Adjusted R Square value of 0.661 indicates that 66.1% of the variation in employee work effectiveness can be explained by personnel management and organizational structure, while the remaining 33.9% is influenced by other factors.